A REVIEW ON SIDDHA SASTRIC MEDICINES EFFECTIVE IN COVID-19 MANAGEMENT AT TPEC COVID CARE CENTRE, VELLORE (International Journal of Ayurveda and Pharma Research, 2021)
Covid-19 is a novel virus that occurs in humans and travels globally very rapidly from person to person. Coronavirus disease is a critical challenge in high population countries such as India. The rising expense of western medicine and its adverse reactions has become an important challenge against Covid-19. Nowadays the traditional medical system and its preparations are for various ailments becoming more popular. South Asia's one of the ancient medicine is the Siddha system of medicine. Kaba Sura Kudineer (KSK) has become a popular Siddha medicine on this pandemic. Previously, Nilavembu Kudineer (NVK) is being used more often during dengue fever, Chikungunya, and swine flu outbreaks, which reduced the mortality rate also. Some other medicines, too, are immensely beneficial. Due to a lack of modern antiviral medications, conventional medical systems in respective countries are now becoming known therapeutics, as a consequence of the pandemic. The second wave of Covid-19 is more virulent than the previous first wave. When compared to the previous, the rate of infection transmission and mortality was also higher. Over the next months, India will be targeted by the third and fourth waves of the Coronavirus infection, posing a greater threat to public health. As a result, some Siddha medicines which are administered and observed in Covid Care Centers reported satisfactory clinical outcomes and feedback reports. To justify the formulations, an attempt has been carried out to analyze the ingredients of medicines using textual evidence. This will enable researchers to evaluate the formulations to explore them in further research.